Analisis Risiko Usahatani Buah Naga pada Kelompok Tani Pucangsari di Desa Jambewangi Kecamatan Sempu Kabupaten Banyuwangi - PANGESTU, DEVILENIA SRIWAHYUNINGRAT; SUDARMA, I MADE; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Risk Analysis of Dragon Fruit Farming in Pucangsari Farmers Group in  Jambewangi Village Sempu District Banyuwangi Regency Dragon fruit is one of the leading commodities in Banyuwangi Regency, East Java. One of the dragon fruit producing villages in Banyuwangi is Jambewangi Village. The purpose of the study are to analyze the increase in dragon fruit farming income, to find sources of risk, and to analyze the risk of production, price and income in the Pucangsari Farmer Group, Jambewangi Village, Sempu District, Banyuwangi Regency. This research used quantitative and qualitative analysis. The results shows that the average income of dragon fruit farmers is IDR 24,756,575,7/year with an average land area of 0,7 hectares. In general, the low risk level is evidenced by the value of KV production of 0,08, price of 0,01, income of 0,07, meaning that farmers avoid the risk of production, price and income in dragon fruit farming. Through this research, this is suggest to dragon fruit farmers who are members of the Pucangsari Farmer's Group to form agricultural cooperatives, the government expects to help provide training in processing dragon fruit into various products that can increase the selling value of dragon fruit in harvest season and for further researchers, it is hoped that they can conduct research on risk management strategies for dragon fruit farming so that the results of the discussion become more complete from this research.